Molecular diagnosis of synovial sarcoma: RT-PCR detection of SYT-SSX1/2 fusion transcripts in paraffin-embedded tissue - Tvrdík, Daniel; Povýsil, Ctibor; Svatosová, Jana; Dundr, Pavel (Medical science monitor, 2005)
BACKGROUND: Synovial sarcomas comprise up to 10 percent of malignant soft tissue tumors, and most are characterized by the chromosomal translocation t(X;18) (pl 1.2;q11.2), which results in the expression of SYT-SSX fusion transcripts. These tumors include two major histological subtypes, biphasic and monophasic. Diagnosing biphasic synovial sarcomas does not usually pose a problem, whereas the monophasic spindle-cell form can be difficult to distinguish from other spindle-cell neoplasms using histological and immunohistochemical profiles only. MATERIAL/METHODS: We investigated the presence of SYT-SSX1/2 chimeric RNA in tumors from 7 patients. We applied amplification of the specific fusion transcripts by reverse transcriptase-polymerase chain reaction (RT-PCR) in fresh, frozen tumors. We also developed a method useful for RT-PCR SYT-SSX fusion transcript detection in formalin-fixed, paraffin-embedded tissue. RESULTS: We found that both histological subtypes of synovial sarcoma were SYT-SSX positive. Moreover, we observed a correlation between histological subtype and type of SYT-SSX fusion transcript. Biphasic synovial sarcoma expressed the SYT-SSX1 fusion transcript, whereas the monophasic subtype expressed the SYT-SSX2 fusion transcript. CONCLUSIONS: The detection of SYT-SSX1/2 fusion transcripts by RT-PCR is a valuable diagnostic marker of synovial sarcoma which can be used for the reclassification of cases whose diagnosis is difficult by routine methods.
Keywords: nádorové proteiny; Male; Chromosomes, Human, X; retrospektivní studie; Sarcoma, Synovial; Česká republika; Transcription, Genetic; Adult; Paraffin Embedding; zalévání tkání do parafínu; Aged; dospělí; translokace genetická; mužské pohlaví; senioři; fúzní onkogenní proteiny; polymerázová řetězová reakce s reverzní transkripcí; lidské chromozomy X; Czech Republic; genetická transkripce; Oncogene Proteins, Fusion; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; Reverse Transcriptase Polymerase Chain Reaction; Translocation, Genetic; Neoplasm Proteins; lidské chromozomy, pár 18; Retrospective Studies; Female; synoviom; lidé středního věku; Chromosomes, Human, Pair 18; nádorové biomarkery; Middle Aged